Mekanisme Pendataan Pajak Barang dan Jasa Tertentu atas Jasa Kesenian dan Hiburan - Putri Noro Arimbi (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
The Practical Work (PKN) was carried out at the Regional Revenue Agency (Bapenda) of Batu City to examine the implementation of the data collection mechanism for the Tax on Certain Goods and Services (PBJT) on Arts and Entertainment Services. This study applied a qualitative approach using observation, interviews, documentation, and literature review to obtain information regarding the implementation of taxpayer data collection activities. The findings indicate that the data collection process is conducted through two mechanisms, namely self-reporting and active data collection. Self-reporting allows taxpayers to register their business, obtain a Regional Taxpayer Identification Number (NPWPD), register tax objects, and update taxpayer information independently. In contrast, active data collection is carried out by Bapenda officers through field activities, including identifying potential taxpayers, distributing registration forms, and verifying business data to ensure its accuracy. The implementation of these mechanisms supports the administration of regional taxes and contributes to improving local revenue. During the implementation process, several obstacles were encountered, including incomplete business documents, limited taxpayer cooperation, and difficulties in conducting field verification. To address these issues, Bapenda performs periodic data updates, direct field visits, administrative verification, and taxpayer education to improve compliance and maintain accurate taxpayer records. Overall, an effective data collection mechanism plays an important role in strengthening regional tax administration and optimizing PBJT revenue from the arts and entertainment services sector.
:: Finalisasi file repositori 22 Juli 2026_Kurnadi
Keywords: data collection mechanism; arts and entertainment services; PBJT